L’invention des commémorations homosexuelles - Régis Schlagdenhauffen (Socio, 2016)
This article focuses on the construction of a homosexual collective memory based on the persecution suffered during World War Two. The analysis of this process shows how a social group, originally stigmatized, succeeded in a relatively short time in reversing its perception within the same society. The reversal process of the stigma, revealed by the commemoration of homosexual victims of nazism, is especially visible in the monuments and requests for inclusion of gays and lesbians in the public commemoration of the martyrs and victims of the Deportation. This article proposes to reconstruct the terms of this process, from 1946 until today.